2013
DOI: 10.1002/gps.3953
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with help‐seeking behaviors in Mexican older individuals with depressive symptoms: a cross‐sectional study

Abstract: Objective Depression in the elderly is associated with multiple adverse outcomes, such as high health service utilization rates, low pharmacological compliance, and synergistic interactions with other comorbidities. Moreover, the help seeking process, which usually starts with the feeling “that something is wrong” and ends with appropriate medical care, is influenced by several factors. The aim of this study was to explore factors associated with the pathway of help seeking among older adults with depressive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 34 publications
3
22
0
2
Order By: Relevance
“…Education level, in a complex model also including gender, health care utilization and the belief that depression is not a disease, has been associated with help-seeking behavior for depressive symptoms in community-dwelling older individuals. 28 Regan et al also demonstrated a significant inverse association between education level and depressive symptoms in older adults. 19 …”
Section: Discussionmentioning
confidence: 90%
“…Education level, in a complex model also including gender, health care utilization and the belief that depression is not a disease, has been associated with help-seeking behavior for depressive symptoms in community-dwelling older individuals. 28 Regan et al also demonstrated a significant inverse association between education level and depressive symptoms in older adults. 19 …”
Section: Discussionmentioning
confidence: 90%
“…Education level, in a complex model also including gender, health care utilization and the belief that depression is not a disease, has been associated with help-seeking behavior for depressive symptoms in community-dwelling older individuals. 28 Regan et al also demonstrated a significant inverse association between education level and depressive symptoms in older adults. 19 There have been several proposed mechanisms for the associations between depression and IBD.…”
Section: Discussionmentioning
confidence: 90%
“…No obstante, es una realidad que, en los países de bajo y mediano ingreso, la posibilidad de recibir tratamiento oportuno y adecuado es limitada 32 . En México, en una encuesta realizada a 2322 AM derechohabientes del Instituto Mexicano del Seguro Social, se encontró que solo el 7.6% de los sujetos con síntomas depresivos contaba con atención adecuada, lo cual se traduce en que más del 90% no la recibe, ya sea porque no la solicitan o porque no se les otorga 34 . Por todo lo hasta aquí señalado, debe considerarse que es necesario identificar las diversas condiciones asociadas a cada tipo particular de depresión e identificar grupos en riesgo para planear intervenciones, para contribuir a abatir la depresión en el AM y sus consecuencias.…”
Section: Discussionunclassified